INVESTIGATING THE MOTIVATION LEVEL OF STUDENTS IN ONLINE LEARNING IN JUNIOR HIGH EDUCATION INSTITUTION DURING PANDEMIC COVID-19 - FARDANI ARFIAN (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2021)
The purpose of this study was to investigate and explore the level of junior high student’s motivation during online learning in pandemic COVID-19. In this design-based research study, motivation level is examined by ARCS survey, interview and observation. The total of respondents were 180 students with different degree levels of study, gender and academic achievement. The analyzed data was measured by SPSS. From this research, the result shows that students of middle degree level have the highest motivation level during pandemic. A statistically significant difference in motivation level is also seen at the beginning of online learning and at the middle of online learning.